DO THE WORK MOTIVATION AND TEACHING EXPERIENCE OF CERTIFIED VOCATIONAL SCHOOL TEACHERS INFLUENCE THEIR PERFORMANCE? - Mus, Taufik; Marpanaji, Eko; Sukardi, Suriany (JURNAL NALAR PENDIDIKAN, 2025)
This study aims to evaluate the extent to which work motivation and teaching experience influence the performance of certified vocational high school teachers in Makassar. The approach used in this study was a quantitative survey involving 134 teachers from three public vocational high schools in Makassar as respondents. The findings indicate that work motivation has a significant impact on teacher performance and contributed to an improvement of 0.58 points in their performance. The majority of teachers fell into the very high (46%) and high (31%) work motivation categories, while most had moderate or medium (49.3%) and low (20%) teaching experiences. Although teacher certification is expected to improve performance, the data show that the performance of certified teachers remains in the medium (34.4%) and low (30.6%) categories. This study emphasizes the importance of enhancing work motivation and continuous professional development to improve the quality of vocational education in Indonesia.